Pancreatic Cancer Imaging: What the Surgeon Wants to Know? - Ajaykumar C. Morani; Ahmed Taher; Nisha S. Ramani; Corey T. Jensen; Asif Patel; Bilal Mujtaba (Thieme Medical and Scientific Publishers Pvt. Ltd., 2020)
Pancreatic cancer is rare but is one of the deadliest cancers. Complete surgical removal of the cancer with negative margins is the only potentially curative treatment. However, majority of the cases present with distant metastases and/or locally advanced disease, and only a limited subset (up to 20%) of patients are surgical candidates. Therefore, accurate staging of pancreatic cancer is very important for treatment planning. It is very important to distinguish between patients who are surgical candidates and those who would need palliative treatment. Imaging plays a crucial role in the detection of the primary tumor, vascular involvement and variants, metastasis, prediction of resectability, and monitoring treatment response. High-resolution multidetector computed tomography (CT) is the primary imaging modality of choice for diagnosing and staging pancreatic cancers. Nevertheless, integration of ultrasound, CT, and magnetic resonance imaging (MRI) may be needed for accurate determination of the tumor extent and optimal management. Herein, we aim to provide a radiological review for "what the surgeon wants to know about pancreatic cancer?" In this review, we highlight the main types of invasive pancreatic cancers and discuss the role of imaging in determining the resectability of pancreatic tumors and the role of neoadjuvant treatment in downstaging borderline or unresectable cases in addition to featuring significant postsurgical complications.